15.51 % efficiency all-small-molecule organic solar cells achieved by symmetric thiazolyl substitution. (1st December 2022) - Wu, Simin; Feng, Wanying; Meng, Lingxian; Zhang, Zhe; Si, Xiaodong; Chen, Yu; Wan, Xiangjian; Li, Chenxi; Yao, Zhaoyang; Chen, Yongsheng
Abstract: Two new small molecule donors of SW1 and SW2 are designed and synthesized by employing thiophene and thiazole substituents as the side groups of benzo[1, 2-b:4, 5-b′]dithiophene central unit, respectively. Due to the more electron-withdrawing feature and enhanced intermolecular stacking of SW2 with respect to that of SW1, the all-small-molecule (ASM) organic solar cells (OSCs) based on SW2 afford a much better power conversion efficiency up to 15.51 %, along with both enlarged open-circuit voltage and fill factor. Further systematic investigation demonstrates that thiazole could act as an excellent building block to optimize the energy levels, molecular stacking as well as microscopic morphologies in ASM systems, leading to the highly efficient ASM-OSCs. Graphical Abstract: ga1 Highlights: ● Thiazole is developed as an effective building block to optimize the energy levels, molecular packings and microscopic morphologies of small molecule donors. ● Two new small molecule donors of SW1 and SW2 are synthesized with thiophene and thiazole substituents as side groups on BDT central unit, respectively. ● SW2-based all-small-molecule organic solar cell exhibits an excellent PCE of 15.51 %.